A Prospective Multicenter Study of Systemic Reactions in Standardized Specific Immunotherapy for Allergic Rhinitis in China. Issue 1 (January 2014) - Chen, Jianjun; Li, Bin; Zhao, Yan; Zhang, Quanming; Wan, Lijia; Liu, Jun; Tian, Xingde; Li, Guoyi; Zhou, Jie; Zhang, Long; Wang, Pengju; Cheng, Qi; et al.
Background: Standardized allergen-specific immunotherapy (SIT) has been used in China for years. However, there is no extensive study of the safety of standardized SIT in Chinese patients until now. The aim of the current study is to perform a prospective and multicenter study to evaluate the systemic reactions (SRs) of standardized SIT in Chinese patients. Methods: The study was performed in 13 allergy centers in China, using the same vaccine and practice procedure. The length of observation period was 2 years. SRs were recorded and analyzed. Results: There were 666 patients included (261 children and 405 adults). All patients finished the initial phase and 47 patients withdrew during the maintenance phase. There were 0.47% (94/19, 963) SRs in all injections (0.72 in children and 0.31% in adults); 8.26% (55/666) patients experienced SRs (12.26% children and 5.68% adults). The occurrence of SRs was significantly higher in children than that in adults (p < 0.01). A higher ratio of SRs was found among patients accompanied with asthma. There were 74.47% SRs of grade I, 15.96% SRs of grade II, 7.45% SRs of grade III, and 2.13% SRs of grade IV. There were 90.43% of SRs associated with the discomfort of lower respiratory tract. Conclusion: This multicenter study showed that properly conducted standardized SIT was a safe treatment for allergic rhinitis in China. The incidence of SRs was higher in children than that in adults.